PENGARUH PROGRAM KESELAMATAN DAN KESEHATAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN - Putri, Annisa Dwi; Bakti, Dadang Karya; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2024)
Occupational Safety and Health (K3) is an inseparable part of employment and human resources. Occupational Safety and Health (K3) is a program created for workers or laborers as well as employers as a form of prevention of work accidents and illnesses resulting from work relations that may occur to workers in the work environment. This research aims to determine the effect of occupational safety and health on employee work motivation at Perum Bulog Lampung Regional Office. This research method uses quantitative research with a sample of 37 employees at Perum Bulog, Lampung Regional Office. Data collection techniques were carried out using questionnaires and documentation. Data analysis using simple linear regression and hypothesis testing. The results of this research show that tcount is 6.193 > ttable 1.691 and the significance value is 0.000 < 0.05. So there is a significant influence between the Occupational Safety and Health variables on employee work motivation.